2004
DOI: 10.1023/b:jtan.0000042160.82063.c4
|View full text |Cite
|
Sign up to set email alerts
|

TG, DTA, FTIR and Raman spectral analysis of Zna/Mgbammonium sulfate mixed crystals

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…Changes occurred during the sorption process and were related to the additional absorption frequencies of ammonium. The results confirmed that the main changes were observed at approximately 1389-1384 cm −1 , attributing to the absorption band of NH 4 + present in the zeolite structure 44 . The normal modes of vibration of a free NH 4…”
Section: Resultssupporting
confidence: 80%
“…Changes occurred during the sorption process and were related to the additional absorption frequencies of ammonium. The results confirmed that the main changes were observed at approximately 1389-1384 cm −1 , attributing to the absorption band of NH 4 + present in the zeolite structure 44 . The normal modes of vibration of a free NH 4…”
Section: Resultssupporting
confidence: 80%
“…Solid State Science and Technology XXIX Figure 1 shows the XRD pattern of Ti:LiNbO 3 crystals obtained at room temperature and the XRD result summarized in Table 2 From Figure 2, well-defined Bragg peaks can be observed at specific 2 theta angles which indicate that the samples are crystalline. The diffraction peaks obtained, together with identified d spacing and hkl values are compared with international centre for diffraction data (ICDD) data and it was confirmed powder XRD results of Ti:LiNbO 3 testify the crystalline nature and purity of the crystal [7][8]. Figure 3 shows the DTA curve of the samples.…”
supporting
confidence: 63%
“…The single crystal EPR studies on Fe(III) [9], Cr(III) [10], VO(II) [11], Cu(II) [12], and Mn(II) [13] doped Tutton's salts are studied. The FT-IR and TG-DTA behaviors of zinc ammonium sulfate and magnesium ammonium sulfate mixed crystals have been investigated [14]. Although extensive studies have been carried out on Tutton's salt crystals, the crystal structure and crystalline perfection of Zn x Mg (1À x) (NH 4 O in various molar proportions (0.10-0.90) were made in triply distilled water and well stirred for 2 h to ensure homogeneity.…”
Section: Introductionmentioning
confidence: 99%